LOGIKA ARISTOTELES: PERKEMBANGAN LOGIKA DAN SESAT BERPIKIR - Indah, Astrid Veranita; Mutahirah, Mutahirah (Sulesana: Jurnal Wawasan Keislaman, 2023)
The logical way of thinking in finding truth has existed since the pre-Socratic era. However, the science that studies logical thinking was written by Aristotle. Aristotle introduced the syllogism consists of premises and a conclusion. A conclusion consists of premises and these premises contain certain conditions. If one of the premises does not contain certain conditions, then a conclusion cannot be drawn.By learning logic, someone will think clearly so that they are not easily provoked by emotions due to the logical fallacy.It is in this thinking activity that it gives the impression to the public how insightful a person's thinking is, whether the person is trying to mislead the listener or simply does not know the rules of logical thinking. The implication of this research is someone will be able to think logically, that they can differentiate and criticize events that occur in life by seeing whether the event makes sense or is in accordance with the rules or not. So that logical thinking becomes a process of thinking wisely that it is not easy to conclusions without considering it carefully.